Simple and Versatile Turbidimetric Monitoring of Bacterial Growth in Liquid Cultures Using a Customized 3D Printed Culture Tube Holder and a Miniaturized Spectrophotometer: Application to Facultative and Strictly Anaerobic Bacteria - Maia, Margarida R. G.; Marques, Sara; Cabrita, Ana R. J.; Wallace, R. John; Thompson, Gertrude; Fonseca, António J. M.; Oliveira, Hugo M. (Frontiers in Microbiology, 2016)
Here we introduce a novel strategy for turbidimetric monitoring of bacterial growth in liquid culture. The instrumentation comprises a light source, a customized 3D printed culture tube holder and a miniaturized spectrophotometer, connected through optical cables. Due to its small footprint and the possibility to operate with external light, bacterial growth was directly monitored from culture tubes in a simple and versatile fashion. This new portable measurement technique was used to monitor the growth of facultative (Escherichia coli ATCC/25922, and Staphylococcus aureus ATCC/29213) and strictly (Butyrivibrio fibrisolvens JW11, Butyrivibrio proteoclasticus P18, and Propionibacterium acnes DSMZ 1897) anaerobic bacteria. For E. coli and S. aureus, the growth rates calculated from normalized optical density values were compared with those ones obtained using a benchtop spectrophotometer without significant differences (P = 0.256). For the strictly anaerobic species, a high precision (RSD < 3.5%) was observed between replicates up to 48 h. Regarding its potential for customization, this manifold could accommodate further developments for customized turbidimetric monitoring, such as the use of light-emitting diodes as a light source or flow cells.